Estimation of vibration powers flowing to and out of a high-speed train bogie frame assisted by time-domain response reconstruction. (1st January 2022) - Wang, Mingyue; Sheng, Xiaozhen; Li, Muxiao; Li, Yaguang
Abstract: Vibration transmitted to a car body through the wheelset, bogie and suspension system is one of the main sources generating interior noise for a high-speed train. In order to derive measures for controlling train interior noise, it is necessary to determine the high-frequency (up to about 1000 Hz) operational forces applied to the bogie frame and to quantify vibration powers input for each force to the car body. These operational forces can be estimated if sufficient measured vibration data of the bogie frame are available. However, since the natural modes of the frame are dense, the number of the forces is large, and the number of sensors which can be installed is limited, measured vibration data are often insufficient to determine the forces and the associated vibration powers. To overcome this difficulty, an approach making use of response reconstruction is developed in this paper. Firstly, a time-domain response reconstruction method based on empirical wavelet transform is applied so that, although measurement is performed for a limited number of locations, responses of the frame at other locations can be reconstructed, giving sufficient response data for force identification. Secondly, with the measured and reconstructed responses, forces are identified using regularization techniques developed for inverse problems. Finally, a power-transfer path analysis is attempted to rank the vibration transmission paths between the bogie frame and the car body. To check the accuracy of the response reconstruction method, responses are reconstructed for certain locations at which the responses are actually measured and it is shown that the reconstructed responses and the measured ones are in good agreement, confirming the effectiveness of the method. In force identification, several regularization techniques are tested and it turns out that the results match well with each other.